Socio Demographic and Headache Characteristics of Migraine Patients in a Tertiary Care Hospital in Bangladesh - Bhattacharjee, Manabendra; Karim, MD Rezaul; Hossain, Akmal; Mondol, Gurudas; Biswas, Rajib (Bangladesh Journal of Neuroscience, 2019)
Migraine is a common type of headache. After tension type headache, it is the second common cause of primary headache disorder with a female preponderance.This cross sectional study was done toassess the sociodemographic characteristics of migraine patients in Bangladeshi population and to see the characteristics of headache and associated comorbidities of migraine patients.The study was conducted in a tertiary care hospital (Mymensingh medical college) of Bangladesh.The study subjects consisted of 60 patients with migraine headache seen in neurology OPD.Mean age was 32.03± 11.74 yrs. Male female ratio was 1: 2.7.Most of them are housewives (61.6%). 22% had family history of headache. Most of the patients had severe (53.4%) and frequent (e”3 per month) headache attacks. Aura was present in 25% patients. Depressive illness was the associated comorbid condition which was found in 15% patients. Bangladesh Journal of Neuroscience 2019; Vol. 35 (1): 22-26